1997
DOI: 10.1038/sj.cdd.4400263
|View full text |Cite
|
Sign up to set email alerts
|

Role of proteases in activation of apoptosis

Abstract: Programmed cell death, or apoptosis, is a physiological cell suicide mechanism, which is triggered in the cells by different stimuli. It has been shown that proteases play a significant role both in the target cell killing by cytotoxic lymphocytes and in the TNF-or anti-Fas-induced cell death. The proteases involved in the early (induction) and late (cell self-destruction) stages of apoptosis are reviewed. It is suggested that the late stages are connected with the activation of a cascade of intracellular prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 31 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…7). Recently, TPCK has been shown to to block the conversion of the inactive 32-kDa caspase-3 precursor into the mature caspase-3 (35), thus providing an explanation of its inhibitory effect on apopotosis reported in several studies (11). It is noteworthy that, under our conditions, no increase in a chymotrypsin activity was observed (Fig.…”
Section: Discussionmentioning
confidence: 44%
“…7). Recently, TPCK has been shown to to block the conversion of the inactive 32-kDa caspase-3 precursor into the mature caspase-3 (35), thus providing an explanation of its inhibitory effect on apopotosis reported in several studies (11). It is noteworthy that, under our conditions, no increase in a chymotrypsin activity was observed (Fig.…”
Section: Discussionmentioning
confidence: 44%
“…4 Whether the caspase cascade and the lysosomal proteolytic pathway intersect during onset of apoptosis is not known. We therefore looked for the involvement of caspases in the apoptotic pathway initiated by CB and CD inhibitors.…”
Section: Apoptosis By Cathepsin Inhibitors Is Caspase-dependentmentioning
confidence: 99%
“…With few exceptions, the caspase system seems to be the most universally involved one. 3,4 Recently, proteases resident within the endosomal-lysosomal compartment (cathepsins) have also been associated with apoptosis. [5][6][7][8][9] These studies demonstrated the need for a cathepsin-mediated proteolytic event in the apoptotic pathway triggered by cytokines or antiblastic drugs.…”
mentioning
confidence: 99%
“…These caspases have been shown to be intracellular and are directly involved in the intracellular events that occur as the cell undergoes apoptosis. Other proteases apart from the caspases have been shown to be activated during apoptosis, including calpains [Squier and Cohen, 1996] and serine proteases [Sukharev et al, 1997].…”
mentioning
confidence: 99%